Penguatan Pendidikan Pancasila Melalui Nilai-nilai Teologis dan Pedagogis Pendidikan Agama Islam dalam Bingkai Kurikulum Merdeka - Sudibyo Sudibyo; Koko Khoerudin (MAN 4 Kota Pekanbaru, 2026)
Pancasila faces complex character crises in the digital era, demanding holistic character education. This qualitative study formulates a comprehensive strategy to strengthen Pancasila values through the theological and pedagogical principles of Islamic Religious Education (IRE) within the Kurikulum Merdeka. Using a narrative literature review of 15 selected journals, the study reveals that IRE functions as the theological-ethical soul of Pancasila. The novelty of this research lies in formulating a practical synergy: integrating religious moderation (wasathiyah) and multicultural strategies into the Pancasila Student Profile (P5). This integration effectively counters radicalism and fosters social solidarity (ukhuwah basyariyah). The study concludes that IRE transcends ritualistic doctrine, acting as a primary catalyst for national character. It successfully bridges individual piety with inclusive civic action, forming a spiritually deep and highly loyal younger generation.